Evaluating the Impact of Home Economics Teachers' Entrepreneurial Activities on Family Economic Stability and Well-Being in Northeast Nigeria - Umoru, Mohammed Lawal (Contemporary Education and Community Engagement (CECE), 2024)
This study examines the impact of entrepreneurial activities of Home Economics teachers on family economic stability and well-being in Northeast Nigeria. Home Economics, as a field, encompasses various disciplines such as nutrition, home management, and consumer education, aiming to improve the quality of life for individuals and families. In Northeast Nigeria, Home Economics teachers often engage in entrepreneurial activities, leveraging their expertise to supplement their income and enhance their families' economic stability. This study evaluates the extent to which these entrepreneurial endeavors contribute to family income, food security, and overall quality of life. Using a cross-sectional survey design, data were collected from Home Economics teachers across Adamawa, Bauchi, Borno, Gombe, Taraba, and Yobe states. A sample of 200 teachers was selected through multistage sampling. The study employed both descriptive and inferential statistics to analyze the data, including paired samples t-tests and W-statistics to test the hypotheses at a 0.05 level of significance. The findings reveal that entrepreneurial activities significantly enhance family economic stability and well-being. Teachers engaged in ventures such as catering, textile and fashion businesses, and home management consultancy experienced notable improvements in family income, food security, and overall quality of life. The study underscores the importance of supporting entrepreneurial initiatives among Home Economics teachers to foster economic resilience and social development in the region. The results provide valuable insights for policymakers, educators, and community leaders to integrate entrepreneurial education within the Home Economics curriculum, thereby promoting sustainable development in Northeast Nigeria.